Erodibility Status of Different Forest Soils in Himachal Pradesh - Singh, R. P.; Gupta, M. K. (Indian Forester, 1991)
The Present Investigation Deals with Tbe Erosional Behaviour of Soils under Different Types of Land Use and forest Cover in Shimla, Bilaspur, Dharamsala and Nurpur forest Divisions of Himachal Pradesh. Suspension Percentage, Clay-moisture Equivalent Ratio, Dispersion and Erosion Ratio and Erosion Index have been Worked Out. Dispersion and Erosion Ratio and Suspension Percentage are Considered the most Elfective Indices of Soil Erodibility in the Present Study. On the Basis of Soil Studies, the Surface Soil of all the Areas is Affected by Sheet Erosion. The Erodibility Status of the Soils under Different Types of Land Uses have been Worked out in the Order: Scrub forest Soil > Orchard Soil > Burned forest Soli > forest Soil.